Propuesta de una metodología de análisis causa raíz de problemas operacionales durante la perforación según pozos A, B y C (2018)
The purpose of this document is to determine a root cause analysis methodology to diagnose the cause of the operational problems presented in well C, and thus generate lessons learned that can prevent operational problems. In the development of the project, a general description of the geology of the area was carried out, along with a diagnosis of operational problems in wells A and B through the use of different flow diagrams, in order to establish the basis of the matrix that will be delivered as the final product of the present project. The flowcharts used were the logical fault tree and the current reality tree. A description of the tools for the root cause analysis is made, in order to make an adequate selection of a flow chart that determines the most efficient procedure when establishing the origin of the operational problem.